Composite material based on titanium niobate and carbon nanofibers and preparation method and application thereof
By introducing composite materials of titanium niobate nanoparticles into the three-dimensional carbon nanofiber network, the problems of uneven lithium deposition and lithium dendrites in lithium metal batteries are solved, and uniform deposition of lithium metal and improved battery performance are achieved.
Patent Information
- Application Number
- CN202211088657.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-09-07
AI Technical Summary
The existing three-dimensional self-supporting structure lithium current collector materials have problems such as uneven deposition of lithium metal, producing lithium dendrites, and resulting in low electrochemical performance of the battery.
Electrospinning method is used to prepare composite materials based on titanium niobate and carbon nanofibers. By introducing lithium-philic titanium niobate nanoparticles into the three-dimensional carbon nanofiber network, it provides more lithium deposition nucleation sites, thereby inducing Uniform deposition of lithium metal.
Effectively reduce the generation of lithium dendrites, improve the cycle life of negative electrode-free lithium metal batteries, and improve the overall rate performance of the battery.
Smart Images

Figure CN116254623B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of nanomaterials, and in particular to a composite material based on titanium niobate and carbon nanofibers, and a preparation method and application thereof. Background Art
[0002] With the booming development of the electric vehicle industry and the widespread popularity of green energy, people have put forward higher demands on the energy density of energy storage devices. However, the current commercial lithium-ion batteries (LIBs) are mainly composed of graphite anodes and metal oxide cathodes, with low energy density, and the maximum energy density is only 250Wh·Kg -1 , which is far from meeting people's demand for energy density. Electrode materials are the core of energy storage and conversion devices. Researchers have been committed to finding high-performance materials that can replace LIB graphite anodes. Metal lithium has an ultra-high theoretical specific capacity (3860mAh g -1 ) and a lower electrochemical potential (-3.040V vs standard hydrogen electrode), so lithium metal batteries have become a research hotspot in the lithium battery field in recent years.
[0003] However, there are two major problems that need to be solved in lithium metal batteries: on the one hand, as lithium metal is deposited unevenly, the volume of the lithium metal negative electrode changes greatly, forming an unstable solid electrolyte interface (SEI) layer, which continuously consumes lithium metal, and the amount of "dead lithium" gradually increases, and the coulombic efficiency decreases; on the other hand, lithium dendrites gradually form and grow as the cycle progresses, eventually piercing the diaphragm, causing a short circuit inside the battery, and may even cause combustion and explosion. Therefore, one of the main research directions of lithium metal batteries is to achieve uniform deposition of metallic lithium, so as to achieve the purpose of inhibiting the growth of lithium dendrites. So far, researchers have proposed a variety of methods and strategies to achieve high-performance lithium metal batteries, such as adding electrolyte additives, modifying diaphragms, constructing artificial SEI layers, and using solid electrolytes. The purpose of these methods is to construct an SEI layer non-in situ to inhibit the growth of lithium dendrites. However, this SEI layer is still very fragile and has limited ability to inhibit lithium dendrites during the cycle.
[0004] In recent years, three-dimensional (3D) self-supporting structures have shown potential application prospects in the modification of three-dimensional current collectors of lithium metal batteries. For the design and construction of the three-dimensional structure of the lithium-carrying current collector, on the one hand, it can avoid uneven current distribution and lithium deposition, effectively buffer deformation and reduce the generation of lithium dendrites, thereby improving the battery cycle life; on the other hand, it increases the specific surface area of the negative electrode, provides more active sites, improves the utilization rate of the negative electrode and the electrochemical reaction kinetics, and is conducive to the improvement of the overall rate performance of the battery. However, the effect of inducing lithium metal deposition by relying solely on the three-dimensionalization of the physical space of the three-dimensional self-supporting structure is limited, and there are still problems such as uneven deposition of lithium metal, generation of lithium dendrites, and low electrochemical performance of the battery.
[0005] Therefore, the prior art still needs to be improved and developed. Summary of the invention
[0006] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a composite material based on titanium niobate and carbon nanofibers and a preparation method and application thereof, aiming to solve the problems of uneven lithium metal deposition, generation of lithium dendrites and lower electrochemical performance of the battery in the existing three-dimensional self-supporting structure lithium-loaded current collector materials.
[0007] The technical solution of the present invention is as follows:
[0008] The first aspect of the present invention provides a method for preparing a composite material based on titanium niobate and carbon nanofibers, which comprises the steps of:
[0009] Providing a first organic solution containing niobium citrate, a second organic solution containing a titanium source and a hydrolysis inhibitor, and a third organic solution containing a spinning polymer and a cyclodextrin;
[0010] Mixing the first organic solution, the second organic solution, and the third organic solution to obtain a mixed solution;
[0011] Using the mixed solution as spinning solution, and performing electrostatic spinning to obtain a composite material precursor;
[0012] The composite material precursor is subjected to pre-oxidation treatment and carbonization treatment in sequence to obtain the composite material based on titanium niobate and carbon nanofibers.
[0013] Optionally, the method for preparing the first organic solution containing niobium citrate comprises the steps of:
[0014] Adding citric acid into water to obtain an aqueous solution of citric acid;
[0015] Under the condition of 60-90° C., adding a niobium source into an aqueous solution of citric acid and stirring until the water evaporates to obtain a niobium citrate solid gel;
[0016] The niobium citrate solid gel is added into a first organic solvent to obtain a first organic solution containing niobium citrate.
[0017] Optionally,
[0018] The molar ratio of the niobium source to citric acid is 1.0:(0.5-5.0);
[0019] And / or, the niobium source is selected from at least one of niobium oxalate and niobium hydroxide;
[0020] And / or, the first organic solvent is selected from at least one of anhydrous ethanol and N,N-dimethylformamide.
[0021] Optionally,
[0022] The titanium source is selected from at least one of titanium trichloride, titanium tetrachloride, and tetrabutyl titanate;
[0023] and / or, the hydrolysis inhibitor is selected from at least one of oxalic acid, citric acid and acetic acid;
[0024] And / or, the solvent in the second organic solution containing the titanium source and the hydrolysis inhibitor is a second organic solvent, and the second organic solvent is selected from at least one of anhydrous ethanol and N,N-dimethylformamide.
[0025] Optionally,
[0026] The spinning polymer is selected from at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polymethyl methacrylate and polyacrylonitrile;
[0027] And / or, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin and γ-cyclodextrin;
[0028] And / or, the solvent of the third organic solution containing the spinning polymer and cyclodextrin is a third organic solvent, and the third organic solvent is selected from at least one of anhydrous ethanol and N,N-dimethylformamide.
[0029] Optionally, the electrospinning process parameters are:
[0030] The spinning voltage is 15-25 keV, the spinning temperature is 60-90°C, and the spinning solution flow rate is 0.6-1.0 mL·h -1 The distance between the metal needle and the collecting drum is 10 to 25 cm.
[0031] Optionally, the atmosphere of the pre-oxidation treatment is an air atmosphere, the temperature of the pre-oxidation treatment is 150 to 250° C., and the time of the pre-oxidation treatment is 2 to 6 hours.
[0032] Optionally, the atmosphere of the carbonization treatment is an inert gas atmosphere, the temperature of the carbonization treatment is 800 to 1100° C., and the time of the carbonization treatment is 1 to 5 hours.
[0033] In a second aspect of the present invention, a composite material based on titanium niobate and carbon nanofibers is provided, wherein the composite material based on titanium niobate and carbon nanofibers is prepared by the preparation method of the present invention as described above, and comprises a three-dimensional carbon nanofiber network and titanium niobate nanoparticles loaded inside and on the surface of the three-dimensional carbon nanofiber network.
[0034] The third aspect of the present invention provides an application of the composite material based on titanium niobate and carbon nanofibers as described above in a negative electrode-free lithium metal battery.
[0035] Beneficial effects: The present invention prepares a composite material based on titanium niobate and carbon nanofibers by an electrospinning method, introduces a lithium-philic dielectric ceramic material titanium niobate into a three-dimensional self-supporting carbon nanofiber network, provides more lithium-philic groups as nucleation sites for lithium deposition, thereby inducing uniform deposition of lithium metal, avoiding uneven current distribution and lithium deposition, and effectively reducing the generation of lithium dendrites. When the composite material based on titanium niobate and carbon nanofibers is used as a self-supporting lithium-carrying current collector material for a negative electrode-free lithium metal battery, the cycle life of the negative electrode-free lithium metal battery can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a scanning electron microscope image of the composite material based on titanium niobate and carbon nanofibers prepared in Example 1 of the present invention.
[0037] Figure 2 This is a transmission electron microscope image of the composite material based on titanium niobate and carbon nanofibers prepared in Example 1 of the present invention.
[0038] Figure 3 This is an X-ray diffraction pattern of the composite material based on titanium niobate and carbon nanofibers prepared in Example 1 of the present invention.
[0039] Figure 4 A graph showing the test results of the cycle performance of a symmetrical battery assembled from the composite material based on titanium niobate and carbon nanofibers prepared in Example 1 of the present invention.
[0040] Figure 5 This is a scanning electron microscope image of the composite material based on titanium niobate and carbon nanofibers prepared in Example 2 of the present invention.
[0041] Figure 6 This is an X-ray diffraction pattern of the composite material based on titanium niobate and carbon nanofibers prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0042] The present invention provides a composite material based on titanium niobate and carbon nanofibers, and a preparation method and application thereof. In order to make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0043] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0044] The three-dimensional self-supporting structure lithium-carrying current collector material only relies on the three-dimensionalization of the three-dimensional self-supporting structure in physical space to induce lithium metal deposition, but the effect is limited. There are still problems such as uneven lithium metal deposition, the generation of lithium dendrites, and the low electrochemical performance of the battery. Therefore, the present invention proposes to further compound the three-dimensional self-supporting structure lithium-carrying current collector material and a substance with lithium affinity to increase the nucleation sites for lithium deposition, thereby inducing uniform deposition of lithium metal. Specifically, an embodiment of the present invention provides a method for preparing a composite material based on titanium niobate and carbon nanofibers, which includes the steps of:
[0045] S1, providing a first organic solution containing niobium citrate, a second organic solution containing a titanium source and a hydrolysis inhibitor, and a third organic solution containing a spinning polymer and cyclodextrin;
[0046] S2, mixing the first organic solution, the second organic solution, and the third organic solution to obtain a mixed solution;
[0047] S3, using the mixed solution as a spinning solution, and performing electrospinning to obtain a composite material precursor;
[0048] S4. Pre-oxidation and carbonization are performed on the composite material precursor in sequence to obtain the composite material based on titanium niobate and carbon nanofibers.
[0049] In this embodiment, a first organic solution containing niobium citrate, a second organic solution containing a titanium source and a hydrolysis inhibitor, and a third organic solution containing a spinning polymer and cyclodextrin are mixed and used as a spinning solution, and spun into a composite material precursor using an electrospinning technique; finally, the composite material precursor is subjected to a pre-oxidation treatment and a carbonization treatment, so that the original organic nanofibers are carbonized into carbon nanofibers to form a carbon nanofiber network, so that the titanium niobate (TiNbO4) nanoparticles obtained by the solid phase reaction are evenly distributed inside and on the surface of the carbon nanofiber network, thereby preparing a composite material based on titanium niobate and carbon nanofibers with a special self-supporting structure and a high degree of microscopic dispersion.
[0050] In the composite material based on titanium niobate and carbon nanofibers in the embodiment of the present invention, a three-dimensional self-supporting carbon nanofiber network is used as a matrix, and TiNbO4 nanoparticles, a lithium-philic dielectric ceramic material, are introduced into the three-dimensional self-supporting carbon nanofiber network. The TiNbO4 nanoparticles provide more lithium-philic groups as nucleation sites for lithium deposition, thereby inducing uniform deposition of lithium metal, avoiding uneven current distribution and lithium deposition, and effectively reducing the generation of lithium dendrites; further, the preparation method in this embodiment can make the TiNbO4 nanoparticles uniformly loaded on the interior and surface of the carbon nanofibers in the three-dimensional self-supporting carbon nanofiber network. The uniform loading of the TiNbO4 nanoparticles provides more uniform nucleation sites for lithium deposition, which is more conducive to inducing uniform deposition of lithium metal, avoiding uneven current distribution and lithium deposition, and effectively reducing the generation of lithium dendrites. When the composite material based on titanium niobate and carbon nanofibers is used as a self-supporting lithium-carrying current collector material for a negative electrode-free lithium metal battery, the cycle life of the negative electrode-free lithium metal battery can be improved. In addition, the self-supporting three-dimensional carbon nanofiber network structure provided by the electrospinning technology in this embodiment can not only provide lithium nucleation space, provide space for accommodating lithium and alleviate the volume expansion of lithium, but also further promote the induced deposition of lithium metal in three-dimensional physical space on the one hand, and on the other hand, carbon nanofibers as a conductive matrix promote the conductivity of TiNbO4 nanoparticles to be greatly improved, thereby further improving the electrochemical stability of the composite material. In addition, the synthesis process of the embodiment of the present invention is simple, green, environmentally friendly and safe; the reaction conditions are easy to obtain, and the applicable objects are wide; it is easy to prepare on a large scale.
[0051] The lithium affinity of TiNbO4 nanoparticles in the composite material based on titanium niobate and carbon nanofibers was verified by first-principles (DFT) calculations. Specifically, the surfaces of graphene and TiNbO4 nanoparticles were studied by first-principles calculations to explore the adsorption energy of lithium metal. The calculation results show that the (110) crystal plane of TiNbO4 nanoparticles has the most favorable Ti site for the adsorption of lithium metal, and the adsorption energy of TiNbO4 nanoparticles (-1.94eV) is much greater than that of graphene (-0.98eV). The larger adsorption energy indicates that the adsorption of lithium metal on TiNbO4 nanoparticles is easier than that on graphene, and the nucleation barrier of lithium metal on TiNbO4 nanoparticles is lower. Therefore, TiNbO4 nanoparticles are conducive to inducing the uniform deposition of lithium metal.
[0052] In this embodiment, cyclodextrin is introduced during the preparation of the composite material based on titanium niobate and carbon nanofibers. On the one hand, the mechanical strength of the carbon nanofibers can be increased, so that the pre-oxidized composite material precursor can still maintain a complete self-supporting structure after calcination at a high temperature of 1000°C or above. On the other hand, cyclodextrin has a structure in which the outer edge is hydrophilic and the inner cavity is hydrophobic. As an inclusion agent, it can form an inclusion complex with the reactant ions, and finally the TiNbO4 nanoparticles are evenly dispersed inside and on the surface of the carbon nanofibers.
[0053] In step S1, in one embodiment, the method for preparing the first organic solution containing niobium citrate comprises the steps of:
[0054] S11, adding citric acid to water to obtain an aqueous solution of citric acid;
[0055] S12, adding a niobium source to an aqueous solution of citric acid at 60-90° C. and stirring until the water evaporates to obtain a niobium citrate solid gel;
[0056] S13, adding the niobium citrate solid gel into a first organic solvent to obtain a first organic solution containing niobium citrate.
[0057] In the present embodiment, since the niobium source cannot be directly dissolved in an organic solvent, but the electrospinning process needs to be carried out under non-aqueous spinning solvent conditions to obtain a better spinning effect, therefore, in the present embodiment, the niobium source is first converted into a niobium citrate solid gel that is easily soluble in an organic solvent, and then the niobium citrate solid gel is dissolved in an organic solvent.
[0058] In step S12, the niobium source can be fully dissolved in the citric acid at a temperature of 60 to 90° C. Specifically, the temperature can be kept at 60 to 90° C. by heating in a water bath.
[0059] In one embodiment, the molar ratio of the niobium source to citric acid is 1.0:(0.5-5.0). Under this molar ratio, the niobium source can be fully dissolved and converted into niobium citrate.
[0060] In one embodiment, the niobium source is selected from at least one of niobium oxalate and niobium hydroxide, but is not limited thereto. In previous attempts, the inventors selected niobium ethanol and niobium chloride as niobium sources, but these niobium sources are particularly sensitive to humidity and are prone to side reactions, which affect the performance of the composite material based on titanium niobate and carbon nanofibers. In further attempts by the inventors, niobium oxalate and niobium hydroxide were selected as niobium sources, which are not only low in price, insensitive to humidity, easy to store, but also fully soluble in citric acid aqueous solution, avoiding the additional use of strong acid and alkali, and have better effects, wherein niobium oxalate is easily soluble in water under heating conditions, and niobium hydroxide is easily soluble in organic oxygen-containing acids such as oxalic acid and citric acid, so that niobium oxalate and niobium hydroxide are easily soluble in citric acid aqueous solution for subsequent reactions.
[0061] In step S13, in one embodiment, the first organic solvent is selected from at least one of anhydrous ethanol and N,N-dimethylformamide, but is not limited thereto. The selected first organic solvent can ensure that niobium citrate is fully dissolved in the first organic solvent, ensuring that a homogeneous spinning solution is successfully prepared subsequently.
[0062] In step S1, in one embodiment, the titanium source is selected from at least one of titanium trichloride, titanium tetrachloride, and tetrabutyl titanate, but is not limited thereto.
[0063] In one embodiment, the hydrolysis inhibitor is selected from at least one of oxalic acid, citric acid, and acetic acid. Usually, titanium sources are very easy to absorb water vapor in the air, undergo hydrolysis and deterioration, and generate precipitated substances, which is not conducive to the preparation of a homogeneous spinning solution. The hydrolysis inhibitor is added to utilize the acidic environment to regulate the hydrolysis equilibrium of the titanium source, and at the same time has a certain coordination and complexing ability. Without introducing other ions, the hydrolysis and precipitation reaction of the titanium source is fully suppressed. Specifically, the titanium source and the hydrolysis inhibitor are added to the second organic solvent to obtain a second organic solution containing the titanium source and the hydrolysis inhibitor.
[0064] In one embodiment, the solvent in the second organic solution containing the titanium source and the hydrolysis inhibitor is a second organic solvent, and the second organic solvent is selected from at least one of anhydrous ethanol and N,N-dimethylformamide, but is not limited thereto.
[0065] In one embodiment, the spinning polymer is selected from at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polymethyl methacrylate, and polyacrylonitrile, but is not limited thereto.
[0066] In one embodiment, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin, but is not limited thereto. In this embodiment, cyclodextrin is introduced in the preparation process of the composite material based on titanium niobate and carbon nanofibers. On the one hand, the mechanical strength of the carbon nanofibers can be increased, so that the composite material precursor after pre-oxidation can still maintain a complete self-supporting structure after calcination at a high temperature above 1000°C; on the other hand, cyclodextrin has a structure with hydrophilic outer edge and hydrophobic inner cavity. As an inclusion agent, it can form an inclusion complex with the reactant ions, and finally make the TiNbO4 nanoparticles uniformly dispersed inside and on the surface of the carbon nanofibers. In one embodiment, the solvent of the third organic solution containing the spinning polymer and cyclodextrin is a third organic solvent, and the third organic solvent is selected from at least one of anhydrous ethanol and N, N-dimethylformamide. Specifically, the spinning polymer and cyclodextrin are added to the third organic solution to obtain a third organic solution containing the spinning polymer and cyclodextrin.
[0067] In step S2, in one embodiment, the step of mixing the first organic solution, the second organic solution, and the third organic solution to obtain a mixed solution specifically includes: after mixing the first organic solution and the second organic solution, adding the third organic solution dropwise, stirring for 8 to 24 hours, to obtain the mixed solution. The third organic solution containing the spinning polymer and cyclodextrin has a relatively high viscosity, and the solutions need to be fully dispersed when mixed.
[0068] In one embodiment, in the mixed solution, the mass ratio of the total mass of solid solute to the mass of organic solvent is (0.2-0.4):1.0. That is, in the mixed solution, the total mass ratio of niobium citrate, titanium source, spinning polymer and cyclodextrin to the total mass of the first organic solvent, the second organic solvent, the third organic solvent and the hydrolysis inhibitor is (0.2-0.4):1.0. Under this mass ratio, the viscosity of the spinning solution is moderate, the size of the spinning fiber is easy to control, and the spinning fiber is easy to shape and maintain flexibility.
[0069] In one embodiment, the molar ratio of the titanium source to the niobium source in the mixed solution is 1.0:1.0. In order to obtain a TiNbO4 compound having a stoichiometric ratio of titanium to niobium of 1.0:1.0 in the molecular formula and avoid unnecessary waste, the molar ratio of the titanium source to the niobium source is limited to 1.0:1.0.
[0070] In step S3, in one embodiment, the electrospinning process parameters are:
[0071] The spinning voltage is 15-25 keV, the spinning temperature is 60-90°C, and the spinning solution flow rate is 0.6-1.0 mL·h -1The distance between the metal needle and the collecting drum is 10 to 25 cm. The purpose of controlling the spinning temperature at 60 to 90°C is to allow the solvent to evaporate quickly, thereby reducing the diameter of the spun carbon nanofibers and making the carbon nanofibers more uniform in thickness.
[0072] In step S4, in one embodiment, the atmosphere of the pre-oxidation treatment is an air atmosphere, the temperature of the pre-oxidation treatment is 150-250°C (specifically, the temperature can be increased to 150-250°C at a heating rate of 1-5°C / min), and the time of the pre-oxidation treatment is 2-6h. In specific implementation, the temperature of the pre-oxidation treatment can be 150°C, 180°C, 200°C, 210°C, 220°C, 230°C or 250°C, etc., and the time of the pre-oxidation treatment is 2h, 3h, 4h, 5h or 6h, etc.
[0073] In step S4, in one embodiment, the atmosphere of the carbonization treatment is an inert gas atmosphere (for example, an argon atmosphere or a nitrogen atmosphere), the temperature of the carbonization treatment is 800-1100°C (specifically, the temperature can be increased to 800-1100°C at a heating rate of 1-5°C / min), and the time of the carbonization treatment is 1-5h. During the pre-oxidation treatment and the carbonization treatment, the titanium source and the niobium source undergo a solid phase reaction to generate TiNbO4, and the organic spinning fiber is completely carbonized to form carbon nanofibers. In specific implementation, the temperature of the carbonization treatment can be 800°C, 850°C, 900°C, 950°C or 1100°C, etc., and the time of the carbonization treatment can be 1h, 2h, 3h, 4h or 5h, etc.
[0074] The embodiment of the present invention also provides a composite material based on titanium niobate and carbon nanofibers, wherein the composite material based on titanium niobate and carbon nanofibers is prepared by the preparation method of the present invention as described above, and includes a three-dimensional carbon nanofiber network and titanium niobate nanoparticles loaded inside and on the surface of the three-dimensional carbon nanofiber network. In a further embodiment, the composite material based on titanium niobate and carbon nanofibers includes a three-dimensional carbon nanofiber network and titanium niobate nanoparticles loaded inside and on the surface of the carbon nanofibers in the three-dimensional carbon nanofiber network. Titanium niobate nanoparticles are lithium-philic substances, which act as nucleation sites for lithium deposition, effectively induce uniform deposition of lithium metal, avoid uneven current distribution and lithium deposition, and effectively reduce the generation of lithium dendrites. The composite material based on titanium niobate and carbon nanofibers is used as a lithium-carrying current collector to improve the electrochemical properties of negative electrode-free lithium metal batteries, such as the cycle performance.
[0075] The embodiment of the present invention also provides an application of the composite material based on titanium niobate and carbon nanofibers as described above in the embodiment of the present invention in a negative electrode-free lithium metal battery. In this embodiment, the composite material based on titanium niobate and carbon nanofibers is used as a self-supporting lithium-carrying current collector material in a negative electrode-free lithium metal battery. The following is a detailed description through specific embodiments.
[0076] Example 1
[0077] The preparation method of the composite material based on niobium titanate and carbon nanofibers is as follows: using niobium oxalate as a niobium source, tetrabutyl titanate as a titanium source, acetic acid as a hydrolysis inhibitor, polyvinyl pyrrolidone as a spinning polymer, γ-type cyclodextrin for cyclodextrin selection, and N,N-dimethylformamide as an organic solvent:
[0078] Dissolve 5.0 mmol of citric acid in 20 mL of deionized water to obtain an aqueous solution of citric acid;
[0079] Under the condition of heating in a water bath at 70° C., 2.5 mmol of niobium oxalate was added to an aqueous solution of citric acid to fully dissolve the niobium oxalate in the aqueous solution of citric acid, and stirred until the water was completely evaporated to obtain a niobium citrate solid gel;
[0080] Dissolving niobium citrate solid gel in 5 mL of N,N-dimethylformamide to obtain a first organic solution; dissolving 2.5 mmol of tetrabutyl titanate and 2 mL of acetic acid in 10 mL of N,N-dimethylformamide to obtain a second organic solution;
[0081] 0.001 mmol of polyvinyl pyrrolidone (molecular weight Mw=1300000) was dissolved in 7.5 mL of N,N-dimethylformamide, and after stirring for 10 hours until fully dissolved, 1.0 mmol of γ-cyclodextrin (molecular weight Mw=1297.12) was added, and stirring was continued for 10 hours to obtain a third organic solution;
[0082] After the first organic solution and the second organic solution are uniformly mixed, the third organic solution is added dropwise and stirred for 8 to 24 hours to obtain a mixed solution;
[0083] The mixed solution (as spinning solution) was loaded into a syringe for electrospinning. The spinning voltage was 18 keV, the spinning temperature was controlled at 70 °C, and the spinning solution flow rate was 0.8 mL·h -1 , the distance between the metal needle and the collecting drum is 18 cm, and a composite material precursor is obtained;
[0084] The composite material precursor was pre-oxidized in air atmosphere: the temperature was raised to 210°C at a heating rate of 5°C / min and kept at this temperature for 2 hours; then carbonized in argon atmosphere: the temperature was raised to 900°C at a heating rate of 1°C / min and kept at this temperature for 2 hours to obtain a composite material based on titanium niobate and carbon nanofibers, the scanning electron microscope image of which is shown in FIG. Figure 1 As shown by Figure 1 It can be seen that the surface of carbon nanofibers is uniformly loaded with TiNbO4 nanoparticles. Figure 2 As shown by Figure 2 It can be seen that TiNbO4 nanoparticles are evenly dispersed in carbon nanofibers, providing sufficient lithium-philic nucleation sites. Its X-ray diffraction pattern is shown in Figure 3 As shown by Figure 3 It can be seen that the phase of the nanoparticles in the obtained composite material is TiNbO4.
[0085] The composite material based on titanium niobate and carbon nanofiber (TiNbO4@CNF) was assembled into a symmetrical battery with a surface capacity of 4 mAh g -1 , then at 2 mA g -1 The charge and discharge current density was tested in cycles and compared with a symmetrical battery assembled with pure lithium foil. The results are as follows Figure 4 As shown by Figure 4 It can be seen that the battery devices assembled with composite materials based on titanium niobate and carbon nanofibers have better cycle stability than the battery devices assembled with metallic lithium.
[0086] Example 2
[0087] The preparation method of the composite material based on niobium titanate and carbon nanofibers is basically the same as that in the embodiment, the only difference is that during the carbonization treatment, the temperature is raised to 1000° C. at a heating rate of 1° C. / min and kept at this temperature for 2 hours.
[0088] The obtained SEM image of the composite material based on niobium titanate and carbon nanofibers is as follows: Figure 5 As shown by Figure 5 It can be seen that the titanium niobate (TiNbO4) prepared under this condition is more densely distributed on the surface of the carbon nanofibers than in Example 1.
[0089] Example 3
[0090] The preparation method of the composite material based on niobium titanate and carbon nanofibers is basically the same as that in the embodiment, the only difference is that during the carbonization treatment, the temperature is raised to 800° C. at a heating rate of 1° C. / min and kept at this temperature for 2 hours.
[0091] The X-ray diffraction pattern of the composite material based on niobium titanate and carbon nanofibers is as follows: Figure 6As shown by Figure 6 It can be seen that the crystallinity of the TiNbO4 nanoparticles prepared under this condition is significantly lower than that of Example 1.
[0092] In summary, the present invention provides a composite material based on titanium niobate and carbon nanofibers, and a preparation method and application thereof. In the composite material based on titanium niobate and carbon nanofibers, a three-dimensional self-supporting carbon nanofiber network is used as a matrix, and TiNbO4 nanoparticles, a lithium-philic dielectric ceramic material, are introduced into the three-dimensional self-supporting carbon nanofiber network. The TiNbO4 nanoparticles provide more lithium-philic groups as lithium deposition nucleation sites, thereby inducing uniform deposition of lithium metal, avoiding uneven current distribution and lithium deposition, and effectively reducing the generation of lithium dendrites; further, the preparation method of the present invention can make the TiNbO4 nanoparticles uniformly loaded on the inside and surface of the carbon nanofibers in the three-dimensional self-supporting carbon nanospinning fiber network, and the uniform loading of the TiNbO4 nanoparticles provides more uniform lithium deposition nucleation sites, thereby being more conducive to inducing uniform deposition of lithium metal, avoiding uneven current distribution and lithium deposition, and effectively reducing the generation of lithium dendrites. When the composite material based on titanium niobate and carbon nanofibers is used as a self-supporting lithium-carrying current collector material for a negative electrode-free lithium metal battery, the cycle life of the negative electrode-free lithium metal battery can be improved. In addition, the present invention uses electrostatic spinning technology to provide a self-supporting three-dimensional carbon nanofiber network structure, which can not only provide space for accommodating lithium to alleviate the volume expansion of lithium, but also further promote the induced deposition of lithium metal in three-dimensional physical space. On the other hand, the carbon nanofiber, as a conductive matrix, promotes the electrical conductivity of TiNbO4 nanoparticles to be greatly improved, thereby further improving the electrochemical stability of the composite material. The present invention has a simple synthesis process, is green, environmentally friendly and safe; the reaction conditions are easy to obtain, and the applicable objects are wide; and it is easy to prepare on a large scale.
[0093] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. A method for preparing a composite material based on titanium niobate and carbon nanofibers, characterized in that: Includes steps: Providing a first organic solution containing niobium citrate, a second organic solution containing a titanium source and a hydrolysis inhibitor, and a third organic solution containing a spinning polymer and a cyclodextrin; Mixing the first organic solution, the second organic solution, and the third organic solution to obtain a mixed solution; Using the mixed solution as spinning solution, and performing electrostatic spinning to obtain a composite material precursor; The composite material precursor is subjected to a pre-oxidation treatment and a carbonization treatment in sequence to obtain the composite material based on titanium niobate and carbon nanofibers; the atmosphere of the carbonization treatment is an inert gas atmosphere, the temperature of the carbonization treatment is 900 to 1100° C., and the time of the carbonization treatment is 1 to 5 hours; The composite material based on titanium niobate and carbon nanofibers includes a three-dimensional carbon nanofiber network and TiNbO4 nanoparticles supported inside and on the surface of the carbon nanofibers in the three-dimensional carbon nanofiber network.
2. The method for preparing a composite material based on titanium niobate and carbon nanofibers according to claim 1, characterized in that: The method for preparing the first organic solution containing niobium citrate comprises the steps of: Adding citric acid into water to obtain an aqueous solution of citric acid; Under the condition of 60-90° C., adding a niobium source into an aqueous solution of citric acid and stirring until the water evaporates to obtain a niobium citrate solid gel; The niobium citrate solid gel is added into a first organic solvent to obtain a first organic solution containing niobium citrate.
3. The method for preparing a composite material based on titanium niobate and carbon nanofibers according to claim 2, characterized in that: The molar ratio of the niobium source to citric acid is 1.0:(0.5-5.0); And / or, the niobium source is selected from at least one of niobium oxalate and niobium hydroxide; And / or, the first organic solvent is selected from at least one of anhydrous ethanol and N,N-dimethylformamide.
4. The method for preparing a composite material based on titanium niobate and carbon nanofibers according to claim 1, characterized in that: The titanium source is selected from at least one of titanium trichloride, titanium tetrachloride, and tetrabutyl titanate; and / or, the hydrolysis inhibitor is selected from at least one of oxalic acid, citric acid and acetic acid; And / or, the solvent in the second organic solution containing the titanium source and the hydrolysis inhibitor is a second organic solvent, and the second organic solvent is selected from at least one of anhydrous ethanol and N,N-dimethylformamide.
5. The method for preparing a composite material based on titanium niobate and carbon nanofibers according to claim 1, characterized in that: The spinning polymer is selected from at least one of polyvinyl pyrrolidone, polyvinyl alcohol, polymethyl methacrylate and polyacrylonitrile; And / or, the cyclodextrin is selected from at least one of α-cyclodextrin, β-cyclodextrin, and γ-cyclodextrin; and / or, the solvent of the third organic solution containing the spinning polymer and cyclodextrin is a third organic solvent, and the third organic solvent is selected from at least one of anhydrous ethanol and N,N-dimethylformamide.
6. The method for preparing a composite material based on titanium niobate and carbon nanofibers according to claim 1, characterized in that: The process parameters of the electrospinning are: The spinning voltage is 15-25 keV, the spinning temperature is 60-90°C, and the spinning solution flow rate is 0.6-1.0 mL·h -1 The distance between the metal needle and the collecting drum is 10 to 25 cm.
7. The method for preparing a composite material based on titanium niobate and carbon nanofibers according to claim 1, characterized in that: The atmosphere of the pre-oxidation treatment is an air atmosphere, the temperature of the pre-oxidation treatment is 150 to 250° C., and the time of the pre-oxidation treatment is 2 to 6 hours.
8. A composite material based on titanium niobate and carbon nanofibers, characterized in that: The composite material based on titanium niobate and carbon nanofibers is prepared by the preparation method described in any one of claims 1 to 7, comprising a three-dimensional carbon nanofiber network and TiNbO4 nanoparticles loaded inside and on the surface of the carbon nanofibers in the three-dimensional carbon nanofiber network.
9. Use of the composite material based on titanium niobate and carbon nanofibers as claimed in claim 8 in a negative electrode-free lithium metal battery.
Citation Information
Patent Citations
Preparation method of titanium niobate / transition metal oxide nanofiber anode material
CN110429260A
Method for preparing Ti0.95Nb0.95O4-C nanofiber negative electrode material through electrostatic spinning
CN111063878A
Titanium niobate-containing negative electrode material for lithium ion battery and preparation method thereof
CN112701289A
KR1016179640000B1